2017
DOI: 10.1007/s00705-017-3390-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of ORF3 accessory protein in replication of cell-adapted porcine epidemic diarrhea virus (PEDV)

Abstract: The ORF3 accessory protein has been shown to impede reverse genetics of cell-culture-adapted porcine epidemic diarrhea virus (PEDV). Its absence or truncated variants are also associated with viral attenuation in vivo. Here, three ORF3 variants (ORF3, ORF3 and ORF3) and their truncated counterparts were investigated for their regulatory role in recovery of cell-adapted PEDV in vitro. We demonstrate that ORF3, but not the truncated form, can inhibit recovery of reverse-genetics-derived PEDV when expressed in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…In our study, we firstly constructed different eukaryotic expression vectors to expression ORF3 protein, and found ORF3 protein distributed in perinuclear cytoplasm, and then shifted for aggregation and concentrated in the nucleate of cytoplasm to form punctate patter. This distribution manner of PEDV ORF3 is similar with one study that ORF3 proteins localizes in the cytoplasm in punctate manner (Ye et al, 2015), but distinguishes from the other report of uniform distribution in cytoplasm diffusely (Wongthida et al, 2017;Kaewborisuth et al, 2018). We speculate that the localization and distribution manner of PEDV ORF3 might be dependent on the virus strain-type-specific differences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we firstly constructed different eukaryotic expression vectors to expression ORF3 protein, and found ORF3 protein distributed in perinuclear cytoplasm, and then shifted for aggregation and concentrated in the nucleate of cytoplasm to form punctate patter. This distribution manner of PEDV ORF3 is similar with one study that ORF3 proteins localizes in the cytoplasm in punctate manner (Ye et al, 2015), but distinguishes from the other report of uniform distribution in cytoplasm diffusely (Wongthida et al, 2017;Kaewborisuth et al, 2018). We speculate that the localization and distribution manner of PEDV ORF3 might be dependent on the virus strain-type-specific differences.…”
Section: Discussionsupporting
confidence: 86%
“…Previous study demonstrated that ORF3 and S are co-localized in several cellular compartments in infected cells, and ORF3 may interact with S during PEDV assembly and consequently exert its activity at this step of virus replication (Kaewborisuth et al, 2018). On the contrary, the ORF3 accessory protein has been reported to impede reverse genetics of cellculture-adapted PEDV, because full-length ORF3, but not the truncated form, can inhibit recovery of reverse-genetics derived PEDV when expressed in trans (Wongthida et al, 2017), and the attenuated PEDV rather than virulent PEDV can grow better in ORF3-expressing Vero cells (Ye et al, 2015). Whereas, much more studies report that infectious PEDV could be rescued from a full-length cDNA clone with intact ORF3.…”
Section: Introductionmentioning
confidence: 99%
“…Virus yields in these cells were found to be similar to those in the parental cells when infected with field strain CH/YNKM-8/2013. A clear increase in infectious virus production was, however, observed with attenuated PEDV strains CV777 and AH-M. Quite a mysterious ORF3 protein was described by Jongkaewwattana's laboratory [13,30]. This intact ORF3 protein, named ORF3 NP12 and derived from the Chinese strain JS-2004-2, was found to block the rescue of the infectious virus when its gene was incorporated into strain PEDV AVCT12 .…”
Section: Discussionmentioning
confidence: 99%
“…Accessory proteins are genus-specific for coronaviruses and only a single accessory protein gene, the ORF3 gene, has been identified in the PEDV genome. PEDV ORF3 encodes an ion channel protein, but it is not essential for PEDV replication (Beall et al, 2016;Wang et al, 2012;Wongthida et al, 2017). Thus, the ORF3 gene was chosen as a model to be replaced with an EGFP gene using the method described in this study.…”
Section: Discussionmentioning
confidence: 99%